Economic Predictors of Differences in Interview Faking Between Countries: Economic Inequality Matters, Not the State of Economy. Issue 3 (17th July 2020) - König, Cornelius J.; Langer, Markus; Fell, Clemens B.; Pathak, Raghuvar Dutt; Bajwa, Nida ul Habib; Derous, Eva; Geißler, Sanja M.; Hirose, Shinichi; Hülsheger, Ute; Javakhishvili, Nino; Junges, Nilve; Knudsen, Birgit; et al.
Abstract : Many companies recruit employees from different parts of the globe, and faking behavior by potential employees is a ubiquitous phenomenon. It seems that applicants from some countries are more prone to faking compared to others, but the reasons for these differences are largely unexplored. This study relates country‐level economic variables to faking behavior in hiring processes. In a cross‐national study across 20 countries, participants ( N  = 3, 839) reported their faking behavior in their last job interview. This study used the random response technique (RRT) to ensure participants' anonymity and to foster honest answers regarding faking behavior. Results indicate that general economic indicators (gross domestic product per capita [GDP] and unemployment rate) show negligible correlations with faking across the countries, whereas economic inequality is positively related to the extent of applicant faking to a substantial extent. These findings imply that people are sensitive to inequality within countries and that inequality relates to faking, because inequality might actuate other psychological processes (e.g., envy) which in turn increase the probability for unethical behavior in many forms.